Hospital Mergers and Referrals in the United States: Patient Steering or Integrated Delivery of Care? - Sayaka Nakamura (SAGE Publishing, 2010)
Many tertiary care hospitals (acquirers) acquire non-tertiary care hospitals (targets), and some of these mergers lead to a significant increase in referrals from the target to the acquirer. This study examines the hospitals' motives for integration and for increasing referrals using hospital discharge data from the Pittsburgh area. I develop and estimate a model of referral choice based on a reputation mechanism. The results suggest that low- or average-quality acquirers exploit their targets' monopoly power to steer patients to the acquirers. Distinguished acquirers, on the other hand, seem to have motives other than patient steering, including the integrated delivery of care.